Charakter prawny opłat publicznych na przykładzie opłaty skarbowej - Antonów, Dobrosława (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
One of the kinds of public tributes are public charges. The basic feature that differentiates the public tribute from other public tributes in particular from taxes is payment. It means that the charge is a financial service for which a citizen receives definite service from the state equivalent service . In principle the height of a charge should cover the cost of the service. At times charges are lower. However, more often charges considerably exceed the value of realized by the state service. Then charges acquire the feature of a tax, namely a gratuitous tribute. Public charges among other things are charged for official acts. The example of such charge is stamp duty regulated in act of 16 November 2006 on stamp duty. Stamp duty is chargeable on individual matters falling within the scope of public administration: performance of an official act, on notification or on request, issuance of a certificate on request, issuance of a permission permit, concession; submission of an instrument of power of attorney or procuration or of a copy, excerpt copy or reproduction thereof — in a matter falling within the scope of public administration or in a judical proceeding. Stamp duty is also chargeable on the performance of an official act, issuance of a certificate or permission permit by an entity other than a government and self-government administration authority, in connection with the performance of tasks falling within the scope of public administration, and on submission to the said entity of an instrument of power of attorney or procuration or of a copy excerpt copy or excerpt thereof. Rates of stamp duty are between 1 złoty and 12 750 złotych. In most cases a stamp duty considerably exceeds the cost and the value of the state service. Thus, a stump duty acquire the feature of a gratuitous tribute and in some cases it resembles a tax. Stamp duty on submission of an instrument of power of attorney or procuration is particulary gratuitous. In fact, in such cases a citizen does not receive any state service for his stamp duty except of an acceptance the documents by court of justice or public administration entity. The charge fallowing within this scope has a feature of a tax.
Keywords: opłata skarbowa; opłata publiczna; charakter prawny opłat